Circulating miRNA profiles provide a biomarker for severity of stroke outcomes associated with age and sex in a rat model - Selvamani, Amutha; Williams, Madison H; Miranda, Rajesh C; Sohrabji, Farida (Clinical science (1979), 2014)
Small non-coding RNA [miRNA (microRNA)] found in the circulation have been used successfully as biomarkers and mechanistic targets for chronic and acute disease. The present study investigated the impact of age and sex on miRNA expression following ischaemic stroke in an animal model. Adult (6 month) and middle-aged (11-12 months) female and male rats were subject to MCAo (middle cerebral artery occlusion) using ET-1 (endothelin-1). Circulating miRNAs were analysed in blood samples at 2 and 5 days post-stroke, and brain miRNAs were analysed at 5 days post-stroke. Although stroke-associated infarction was observed in all groups, infarct volume and sensory-motor deficits were significantly reduced in adult females compared with middle-aged females, adult males or middle-aged males. At 2 days post-stroke, 21 circulating miRNAs were differentially regulated and PCA (principal component analysis) confirmed that most of the variance was due to age. At 5 days post-stroke, 78 circulating miRNAs exhibited significantly different regulation, and most of the variance was associated with sex. A small cohort (five) of miRNAs, miR-15a, miR-19b, miR-32 miR-136 and miR-199a-3p, were found to be highly expressed exclusively in adult females compared with middle-aged females, adult males and middle-aged males. Predicted gene targets for these five miRNAs analysed for KEGG (Kyoto Encyclopedia of Genes and Genomes) pathways revealed that the top ten KEGG pathways were related to growth factor signalling, cell structure and PI3K (phosphoinositide 3-kinase)/Akt and mTOR (mammalian target of rapamycin) signalling. Overall, the pattern of circulating miRNA expression suggests an early influence of age in stroke pathology, with a later emergence of sex as a factor for stroke severity.